PENGARUH EFEKTIVITAS KEPEMIMPINAN DAN KINERJA KARYAWAN TERHADAP PENJUALAN DI FLOBAMORA MALL KUPANG - Ronald P.C. Fanggidae (Universitas Nusa Cendana, 2015)
The aim of this study is to know about the correlation between the leadership effectiveness to employees performance and sale. So, this hypothesis that is proposed in this study will show positifcorrelation between them. The concepts that used in this study are the leadership effectiveness,employees performance, perception and sale. The sample method in this study used saturationsample where a group of subject as the sample. The subject of this study were employee who work inFlobamora Mall Kupang. Collecting the data was used questionnaire, development of dataprocessed used simple regression analysis that is corrected item to total from SPSS 11.00 ForWindow to measure validity and realibility. Besides that, using of Kolmogorov-Smirnov andcorrelation measurement to measure normalitation. The result of this study shows that there issignificant leadership effectiveness to employees performance and sale. Keywords: Leadership Effectiveness, Employees Performance and Sale